2020
DOI: 10.18502/cmm.6.2.2695
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Candida africana in oral candidiasis: First report among cancer patients in Iran

Abstract: Background and Purpose: Oropharyngeal candidiasis (OPC) is a fungal infection of the oral cavity caused by the members of C. albicans complex. Although C. africana, as a part of the complex, is considered to be mostly responsible for the development of vulvovaginal candidiasis, it may be associated with a wider clinical spectrum. Case report: This report described two cases diagnosed with oral candidiasis during the receipt of treatment for malignancies. Conventional and molecular tests were performed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Regarding the susceptibility of vaginal C africana and C dubliniensis isolates to different antifungal drugs, previous studies showed that these yeasts are generally sensitive to several commonly used antimycotics 23,35,41 . However, there are some reports showing that C africana exhibits antifungal susceptibility patterns different from those of C albicans 23 and some isolates have been classified as resistant to itraconazole, fluconazole, voriconazole, clotrimazole, 5‐flucytosine and terbinafine 12,22,23,25 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the susceptibility of vaginal C africana and C dubliniensis isolates to different antifungal drugs, previous studies showed that these yeasts are generally sensitive to several commonly used antimycotics 23,35,41 . However, there are some reports showing that C africana exhibits antifungal susceptibility patterns different from those of C albicans 23 and some isolates have been classified as resistant to itraconazole, fluconazole, voriconazole, clotrimazole, 5‐flucytosine and terbinafine 12,22,23,25 …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that most of vaginal C africana isolates from Iran exhibit resistance to various antifungal drugs, 21,22 and ~28% of world isolates appear to be resistant to itraconazole 23 . Furthermore, although C africana is generally associated with vaginal infections, in Iran, this pathogen has also been reported as a cause of paediatric candiduria, 24 and/or oropharyngeal candidiasis in cancer patients 25 . From these latter patients, fluconazole‐ and amphotericin B‐resistant isolates have been also recovered 25 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the tests were carried out in duplicate. The MIC breakpoints were defined for each antifungal agent as follows: fluconazole (susceptible MIC ≤ 8 µg/mL; resistant MIC > 8 µg/mL), amphotericin B (susceptible MIC ≤ 1 µg/mL; resistant MIC > 1 µg/mL), and caspofungin (susceptible MIC ≤ 0.25 µg/mL; resistant MIC ≥ 1 µg/mL) (12).…”
Section: Antifungal Susceptibility Testingmentioning
confidence: 99%
“…However, some reports have shown that the antifungal susceptibility patterns of C. africana and C. dubliniensis are slightly different from those of C. albicans [5,6]. Moreover, based on previous studies, some C. africana isolates have been classified as resistant to itraconazole, fluconazole, voriconazole, clotrimazole, 5-flucytosine, and Terbinafine [4,7,8]. Echinocandins is the first-line antifungal drug for the treatment of Candida infections and has shown prolonged post antifungal effect and concentration-dependent killing activity against the majority of Candida species, including the C. albicans complex [9,10] polymerase chain reaction (PCR) amplification of the hyphal wall protein 1 (HWP1) gene [11].…”
Section: Introductionmentioning
confidence: 99%